A HISTORICAL STUDY OF CONTRIBUTION OF MUGHALS FOR THE DEVELOPMENT OF THE TOURISM INDUSTRY IN JAMMU AND KASHMIR - Yousuf Rather, Aqib (RADJA PUBLIKA, 2022)
The tourism literature of today frequently combines all of the Mughal contributions to Kashmir. Kashmir had a significant role in the magnificent Mughal Empire. The Valley was close to the Central Asian border in the Kabul area. Strong dynastic monarchs like Akbar, Jahangir, Shah-i-Jahan, and Aurangzeb ruled it. The region's trade and commerce were boosted by the Mughals' conquest because it put an end to the region's long-running domestic fighting, built a centralized government, did away with toll charges, and improved and widened its highways. The damaged economy of the province was also fixed by the maintenance of stability and the agriculture system changes. By taking a number of initiatives for the development of the tourism industry in Jammu and Kashmir, it protected the region's emperors from squandering their enormous wealth on the construction of temples, parks, and wellness resorts and inns, effectively transforming the territory into a